1998
DOI: 10.1074/jbc.273.34.21692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonlamellar-prone Lipids on the ATPase Activity of SecA Bound to Model Membranes

Abstract: The effect of nonlamellar-prone lipids, diacylglycerol (DG) and phosphatidylethanolamine (PE), on the ATPase activity of SecA was examined. When Escherichia coli PE of the standard vesicles composed of 60 mol% of this lipid and 40 mol% of dioleoylphosphatidylglycerol (DOPG) is gradually replaced with either dioleoylglycerol (DOG) or dioeloyl PE (DOPE), the ATPase activity of SecA present together increased appreciably. On the other hand, when E. coli PE of the standard vesicles was replaced with DOG analogs, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
(34 reference statements)
2
20
0
1
Order By: Relevance
“…Moreover, it was demonstrated that the property of forming a non-bilayer structure of the membrane is essential for an efficient protein transport across the plasma membrane of E. coli (19). Consistent with this result, recent data indicate that non-bilayer lipids (and their structures) stimulate the activities of the SecA (20) and SecYEG complexes (21). However, it is still unclear how signal peptides induce the formation of a non-bilayer structure.…”
supporting
confidence: 70%
“…Moreover, it was demonstrated that the property of forming a non-bilayer structure of the membrane is essential for an efficient protein transport across the plasma membrane of E. coli (19). Consistent with this result, recent data indicate that non-bilayer lipids (and their structures) stimulate the activities of the SecA (20) and SecYEG complexes (21). However, it is still unclear how signal peptides induce the formation of a non-bilayer structure.…”
supporting
confidence: 70%
“…When it is retracted from SecYEG, SecA could interact directly with the phospholipid bilayer, which would then have the opportunity to drive conformationally specific changes in SecA that could contribute to a carefully controlled progression of the overall conformational reaction cycle. Such interactions could account for the acceleration in the rate of preprotein translocation in the presence of bilayer destabilizing lipids (26), which increase the solvent exposure of the hydrocarbon moieties of the phospholipids (29).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of SecA to interact with the hydrocarbon region of phospholipids in bilayer membranes is also supported by several experiments conducted using vesicles containing acidic phospholipids (26, 28 -30). Bilayer destabilizing lipids increase hydrocarbon exposure (29) and accelerate the rate of both preprotein translocation (26) and a conformational change that can be induced in SecA by interaction with vesicles (30). Moreover, SecA can be labeled by lipids containing photoactivatable groups in their hydrocarbon moieties (31,32) when such probes are incorporated into pure lipid vesicles, although experiments of this kind also indicate that SecA becomes shielded from such interactions when it binds to SecYEG (14,32).…”
mentioning
confidence: 99%
“…SecA is water-soluble, but due to the nature of its activity has an intimate association with the lipid bilayer. It has been reported that acidic lipids and those that do not form lamellae increase SecA ATPase activity (28,29). Moreover, reports show that acidic phospholipids are required for protein translocation (39).…”
Section: Molecular Mass (Kda)mentioning
confidence: 99%
“…The basal ATPase activity of SecA is partially increased by the presence of acidic phospholipids and then fully stimulated by addition of vesicles containing SecYEG and precursor protein (28,29). The mechanism for this regulation is not clear.…”
mentioning
confidence: 99%